The Role of Diffusion Kurtosis MR Imaging in the Evaluation of Invasive Breast Cancer Classification and its Correlation with Prognostic Factors: A Prospective Study of Primarily Advanced Stage Cancers - Yan Gu; Ning Wang; Guangyu Hao; Jing Sun; Wenguo Tan; Ling Yang; Xinxing Ma; Qianqian Wang; Ximing Wang; Chunhong Hu; Mo Zhu (Clinical and Experimental Obstetrics & Gynecology)
Background: The present exploration is aimed to determine whether diffusion kurtosis imaging (DKI)-derived mean diffusivity (MD) and mean kurtosis (MK) are possible parameters for the invasive breast cancer grading and whether MD/MK is related to breast cancer clinical-pathologic factors including estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER-2) and Ki-67. Methods: Tumors from 108 invasive breast carcinoma patients (45.6 ± 11.2 years old; range, 20–84 years), diagnosed by pathological examination between January 2016 and August 2017, were included. DKI data (with b values of 0, 1000, 2000 sec/mm2) and MD/MK were measured. The expression of ER, PR, HER-2, and Ki-67 was evaluated by immunohistochemistry. Results: It was found that MD was significantly lower in grade III breast cancer than in grade II breast cancer (0.82 ± 0.21 vs 1.17 ± 0.24, p < 0.0001), while MK was significantly higher in grade III breast cancer than that in grade II breast cancer (1.00 ± 0.31 vs 0.85 ± 0.21, respectively; p < 0.05). In addition, MD was negatively associated with Ki-67 level (r = –0.39, p < 0.05), while MK was positively associated with Ki-67 level (r = 0.56, p < 0.05). Furthermore, MD was significantly increased in ER and PR positive expression group compared with ER and PR negative expression group, while there is no significant difference of MK in ER and PR positive expression group compared with ER and PR negative expression group. Additionally, there is no significant difference of MD and MK in HER-2 positive expression group compared with HER-2 negative expression group. Conclusions: These results demonstrate that DKI has value in the evaluation on the classification of invasive breast carcinoma. MD values were associated with breast cancer clinical-pathologic factors. DKI can provide useful information in the assessment of tumor proliferation activity.